MONOTOWN IDENTITY AND PROBLEMS OF INDUSTRIAL MENTALITY (ON EXAMPLE OF MAGNITOGORSK) - Davydov, D.A. (Perm Federal Research Centre Journal, 2015)
The article investigates the identity of Magnitogorsk residents. It proves the futility of positioning Magnitogorsk as “the capital of Russian iron and steel works”. Along with economic diversification there is some need for mental diversification in Magnitogorsk and other similar cities. The author points out that proletarian mythology of “a provincial city of steel workers” (city-factory) is not popular among young people causing an outflow of human capital. The author substantiates the need for a large-scale transformation of urban identity in the direction of non-industrial components (including direct transformation of cultural landscape). At the same time the author identifies some structural barriers that prevent the independent resolving of Magnitogorsk identity crisis (costs of bureaucracy, “a symbolic rent” of city-forming enterprise and the lack of civic initiatives). Therefore the author justifies the need for major investments in the city image by the federal center.